Unleashing Competence: Exploring the Influence of Organizational Culture, Emotional Intelligence and Learning Organization - Ariawan; Emba; Daud, Ilzar; Novrianto, Andry; Kurniawan, Muhammad Sani (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aimed to examine the influence of organizational culture, emotional intelligence, and organizational learning on employee competence in the government of Gorontalo City. Data were collected from a sample of 134 government employees, and hypothesis testing was conducted to analyze the significance of the variables. The results indicated that all three factors, namely organizational culture, emotional intelligence, and organizational learning, significantly and positively influenced employee competence. The findings highlighted the importance of fostering a positive and inclusive organizational culture that motivates employees to enhance their competence. Emotional intelligence emerged as a crucial factor in self-motivation, resilience, and empathy, which contributed to improved competence. Additionally, organizational learning played a significant role in supporting continuous professional growth and the development of job-relevant competencies. The analysis of R-Square revealed that organizational culture, emotional intelligence, and organizational learning explained 73.8% of the variance in employee competence. However, it is important to acknowledge that other unexplored factors may also influence competence. These findings have important implications for the government of Gorontalo City. By prioritizing a positive organizational culture, nurturing emotional intelligence, and promoting organizational learning, the government can enhance employee competence, overall performance, and service delivery to the community. Future research should consider investigating additional factors to gain a more comprehensive understanding of competence in the government context. Implementing interventions and strategies to strengthen organizational culture, enhance emotional intelligence, and support continuous learning can further improve employee competence and contribute to the success of the government of Gorontalo City.